Analysis Of Factors Affecting Internet Consumption Among Upper Secondary Students - Limbong, Lustawi; Suhud, Usep; Wibowo, Agus (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research wants to identify the factors influencing the use of the internet data package for students of the Senior High School level, particularly students with an age range of 14 to 18 years. The result of the research, through a survey of 115 respondents, shows that the use of the data package is on account of academic need, with the greater share being online learning and learning materials. This is evidenced by the fact that 80% of the respondents use the internet for academic-related issues, such as doing homework and holding online classes. While 60% use the consumed quota for entertainment purposes—social media, video streaming, online games, and the like—the remaining ones, 45%, choose a price that fits their budget, based on either offered promos or rates and services. Next, a 40% social influence follows a recommendation from the social environment. Up to 55% of the respondents base their selection and consumption of package data on the technological infrastructure, to mean the availability of digital gadgets and quality network. In such a way, content analysis has been used in this study to discern consumption patterns. Of the test results from this research, it is believed that it will further improve the understanding of trends in using package data for high school students and their associates to improve the availability and quality of Internet services for academic purposes.